The Artistic Object and Its Worlds : Literature and Cinema - Ungureanu, Delia,; Wood, Michael, (Contemporary Cinema ;, 2025)
"The best way of being an artist is not to serve a particular art." The film critic André Bazin believed artists create without boundaries in mind. Literary criticism should be no different. This book is a unique collection that critically reflects on the complex, non-unidirectional, and organic relationship between cinema, literature, photography, and the other arts. With essays by David Damrosch, Laura Marcus, Ignacio Sánchez Prado, Maria Dabija, and Michael Makarovsky among others, this volume establishes a much needed dialogue between the fields of world literature and world cinema.